2021
DOI: 10.1371/journal.pone.0260672
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with acceptance of COVID-19 vaccine among University health sciences students in Northwest Nigeria

Abstract: Students of the health sciences are the future frontliners to fight pandemics. The students’ participation in COVID-19 response varies across countries and are mostly for educational purposes. Understanding the determinants of COVID-19 vaccine acceptability is necessary for a successful vaccination program. This study aimed to investigate the factors associated with COVID-19 vaccine acceptance among health sciences students in Northwest Nigeria. The study was an online self-administered cross-sectional study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 44 publications
(48 reference statements)
8
42
2
Order By: Relevance
“…In one report from the United States by Lucia et al [ 40 ], 23% of medical students surveyed were unwilling to take a COVID-19 vaccine even after approval by the Food and Drug Administration. In comparison, studies conducted among Sudanese, Egyptian, Nigerian and Ugandan medical students have generally shown higher COVID-19 vaccine hesitancy rates ranging from 30% to 60% [ 41 , 42 , 43 , 44 ]. Concerns around vaccine safety and efficacy, trust in health authorities, healthcare costs, and experience in the healthcare field were some of the major drivers of vaccine hesitancy in these studies [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one report from the United States by Lucia et al [ 40 ], 23% of medical students surveyed were unwilling to take a COVID-19 vaccine even after approval by the Food and Drug Administration. In comparison, studies conducted among Sudanese, Egyptian, Nigerian and Ugandan medical students have generally shown higher COVID-19 vaccine hesitancy rates ranging from 30% to 60% [ 41 , 42 , 43 , 44 ]. Concerns around vaccine safety and efficacy, trust in health authorities, healthcare costs, and experience in the healthcare field were some of the major drivers of vaccine hesitancy in these studies [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It showed a lack of association between education and vaccine hesitancy, which contrasts with the results of studies in HIC [ 29 ]. Another study in Northwest Nigeria examined attitudes towards the COVID-19 vaccine among health science students [ 30 ]. The study found that older age, instructions by the heads of institutions, trust in government, and readiness to pay for the vaccine positively impacted vaccine acceptance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Northwest Nigeria examined attitudes towards the COVID-19 vaccine among health science students [ 30 ]. The study found that older age, instructions by the heads of institutions, trust in government, and readiness to pay for the vaccine positively impacted vaccine acceptance [ 30 ]. A third study showed that willingness to take the vaccine is higher among people living in LMICs than in the USA and Russia (80.3%, 64.6%, and 30.4% of the population willing to take the vaccine, respectively) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In separate studies conducted in Nigeria, Reuben et al [9] and Adigwe [7] reported low COVID-19 acceptance of 29.0% and 22.7% among residents of northcentral Nigeria and the Federal Capital Territory (FCT), Abuja, respective. In the same vein, although 55.5% COVID-19 acceptance were among health care workers in the southwest and south-south geopolitical zones of Nigeria [10], a lower rate, 40.0%, was however reported among medical students in the Northwestern geopolitical zone in Nigeria [11].…”
mentioning
confidence: 94%